Neural Correlates of Abnormal Temporal Discrimination in Unaffected Relatives of Cervical Dystonia Patients - Narasimham, Shruti; McGovern, Eavan M.; Quinlivan, Brendan; Killian, Owen; Beck, Rebecca; O’Riordan, Sean; Hutchinson, Michael; Reilly, Richard B. (Frontiers in Integrative Neuroscience, 2019)
Background An abnormal temporal discrimination threshold in cervical dystonia is considered to be a mediational endophenotype; in unaffected relatives it is hypothesised to indicate non-manifesting gene carriage. The pathogenesis underlying this condition remains unknown. Investigation of the neural networks involved in disordered temporal discrimination may highlight its pathomechanisms. Objective To examine resting state brain function in unaffected relatives of cervical dystonia patients with normal and abnormal temporal discrimination. We hypothesized that the endophenotype, an abnormal temporal discrimination, would manifest as altered connectivity in relatives in regions associated with cervical dystonia, thereby illuminating the neural substrates of the link between temporal discrimination and cervical dystonia. Methods Rs-fMRI data was analysed from two sex- and age-matched cohorts: 16 unaffected relatives of cervical dystonia patients with normal temporal discrimination and 16 with abnormal temporal discrimination. Regional and whole brain functional connectivity measures were extracted via Independent Component Analysis (ICA), Regional Homogeneity (ReHo) and Amplitude of Low Frequency (ALFF) analyses. Results Our ICA analysis revealed increased connectivity within both the executive control and cerebellar networks and decreased connectivity within the sensorimotor network in relatives with abnormal temporal discrimination when compared to relatives with normal temporal discrimination. The ReHo and ALFF analyses complimented these results and demonstrated connectivity differences in areas corresponding to motor planning, movement coordination, visual information processing, and eye movements in unaffected relatives with abnormal temporal discrimination. Conclusion Disordered connectivity in unaffected relatives with abnormal temporal discrimination illuminates neural substrates underlying endophenotype expression and supports the hypothesis that genetically determined aberrant connectivity, when later coupled with unknown environmental triggers, may lead to disease penetrance.